2022
DOI: 10.3390/agronomy12102325
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilizer with Bacillus pumilus TUAT1 Spores Improves Growth, Productivity, and Lodging Resistance in Forage Rice

Abstract: Bacillus pumilus strain TUAT1 is a plant growth-promoting bacterium (PGPB) applied as a biofertilizer, containing its spores, for rice. In this study, we analyzed the short-term effects of biofertilization on plant growth in the nursery and long-term effects on plant vegetative growth, yield, and lodging resistance in paddy fields using animal feed rice (‘Fukuhibiki’ and line LTAT-29 which was recently officially registered as a cultivar ‘Monster Nokodai 1′) and fodder rice (line TAT-26). The effects of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…2019 , Agake et al. 2021 , 2022a , 2022b ), we focused on roots. A significant increase in root dry weight by B. pumilus TUAT1 inoculation was observed in WT, lym1-2 and cerk1-2 plants, whereas lym3-2 mutant plants showed no increase in root weight ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2019 , Agake et al. 2021 , 2022a , 2022b ), we focused on roots. A significant increase in root dry weight by B. pumilus TUAT1 inoculation was observed in WT, lym1-2 and cerk1-2 plants, whereas lym3-2 mutant plants showed no increase in root weight ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2018 , 2019 , 2020 , Agake et al. 2021 , 2022a , 2022b , Hasibuan et al. 2021 ) and Arabidopsis ( Borjigin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some biofertilizers seem to stimulate tillering in grasses. For example, Agake et al [ 45 ] found an increased tillering rate in two of three varieties of rice inoculated with Bacillus pumilus (approximately 15–30%). In addition to the increased tiller number, these authors were able to detect a statistically higher plant height in biofertilized plants than in control plants.…”
Section: Discussionmentioning
confidence: 99%
“…The complex interactions in nature can mask the effects of biofertilizers, making it difficult to reproduce at field the positive results observed in laboratory [15,178,179]. Along the same lines, the selectivity of the microorganisms towards certain crops may result in different responses to biofertilizer inoculation, with certain plant species showing a higher growth-promoting effect than others [22,178], which highlights the potential of "tailored fertilizers", previously reported.…”
Section: Environmental Aspectsmentioning
confidence: 95%
“…Considering that the effectiveness of biofertilizers can be influenced by several factors (e.g., type and concentration of microorganisms, method of application, crop, or environmental conditions) [3,4], it is common for a microbial strain that exhibits good performance in vitro to perform poorly in field trials [177]. The complex interactions in nature can mask the effects of biofertilizers, making it difficult to reproduce at field the positive results observed in laboratory [15,178,179]. Along the same lines, the selectivity of the microorganisms towards certain crops may result in different responses to biofertilizer inoculation, with certain plant species showing a higher growth-promoting effect than others [22,178], which highlights the potential of "tailored fertilizers", previously reported.…”
Section: Environmental Aspectsmentioning
confidence: 99%